Examining the Effects of the Recent AML/CFT Legislation in Mauritius - Fulena, Viraj; Chittoo, Hemant B.; Bolli, D. Gaël Henriette (APPS Publications, 2023)
This paper focuses on examining the implications of money laundering in Mauritius and providing recommendations to mitigate its negative effects. Another objective of this study is to assess the effectiveness of antimoney laundering (AML) efforts by financial institutions in Mauritius, which was accomplished through the analysis of both primary and secondary data. The research targets professionals in the compliance and in the AML field within the financial sector of Mauritius. Through qualitative interviews of AML professionals and a quantitative survey of 209 respondents, the study reveals a positive relationship between variables related to money laundering. The findings indicate that 86% of the respondents consider the initiatives taken by the Mauritian government to combat money laundering on the island as ineffective. Based on primary data obtained from participants in Mauritius’ financial institutions, there is disagreement regarding the efficacy of the country’s AML legislation in combating money laundering. Furthermore, secondary statistics reveal that the introduction of the AML rules and regulations in 2018, as well as the establishment of the Financial Intelligence Unit (FIU), were responses to a significant increase in suspicious transactions in Mauritius between 2003 and 2014. The study contributes to existing knowledge and highlights the importance of proactive measures to combat money laundering in Mauritius.